2014
DOI: 10.4049/jimmunol.1301628
|View full text |Cite
|
Sign up to set email alerts
|

Follicular B Cells in Thyroids of Mice with Spontaneous Autoimmune Thyroiditis Contribute to Disease Pathogenesis and Are Targets of Anti-CD20 Antibody Therapy

Abstract: B cells are required for development of spontaneous autoimmune thyroiditis (SAT) in NOD.H-2h4 mice where they function as important antigen presenting cells (APCs) for activation of CD4+ T cells. Depletion of B cells using anti-CD20 effectively inhibits SAT development. The goals of this study were to characterize the B cells that migrate to thyroids in SAT, and determine if anti-CD20 effectively targets those B cells in mice with established SAT. The results showed that most thyroid infiltrating B cells in mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 61 publications
1
26
0
Order By: Relevance
“…These results suggest that Th1 and Th17 cells, or CD4+ T cells that produce both Th1 and Th17 cytokines, may both have a pathogenic role in SAT. In our colony of NOD.H-2h4 mice, IFN-γ is absolutely essential for SAT development, and CD4+ T cells expressing IFN-γ and TNF-α are much more prevalent in thyroid infiltrates of mice with SAT than are IL-17-producing CD4 + T cells (Hong & Braley-Mullen, 2014;our unpublished results). Others also showed that IFN-γ-and IL-12-producing cells are present in thyroids of mice with SAT and are increased in areas where there are accumulations of inflammatory cells (Bonita et al, 2003).…”
Section: Ifn-γ Is Required For Development Of Satmentioning
confidence: 75%
See 4 more Smart Citations
“…These results suggest that Th1 and Th17 cells, or CD4+ T cells that produce both Th1 and Th17 cytokines, may both have a pathogenic role in SAT. In our colony of NOD.H-2h4 mice, IFN-γ is absolutely essential for SAT development, and CD4+ T cells expressing IFN-γ and TNF-α are much more prevalent in thyroid infiltrates of mice with SAT than are IL-17-producing CD4 + T cells (Hong & Braley-Mullen, 2014;our unpublished results). Others also showed that IFN-γ-and IL-12-producing cells are present in thyroids of mice with SAT and are increased in areas where there are accumulations of inflammatory cells (Bonita et al, 2003).…”
Section: Ifn-γ Is Required For Development Of Satmentioning
confidence: 75%
“…For example, when SAT develops following Treg depletion in NP-Tg NOD.H-2h4 mice, there are many B cells in the thyroid infiltrates, but all B cells are NP-specific and do not secrete Ig (Yu, Maiti, et al, 2006), suggesting that their function in the thyroid is to present antigen and not to secrete autoantibody. Splenic B cells in NOD.H-2h4 mice include marginal zone (MZ), follicular (FO), and T2 subsets based on differential expression of CD21 and CD23 (Hong & Braley-Mullen, 2014;Yu, Dunn, et al, 2008), and essentially all B cells that traffic to the thyroid are FO B cells (Hong & Braley-Mullen, 2014). We believe that FO B cells are the primary effector and antigen-presenting cells in SAT, based on their upregulation of MHC class II during disease development, their presence in thyroid infiltrates and the fact that anti-CD20, which has relatively little effect on MZ B cells in adult NOD.H-2h4 mice, but depletes most FO B cells (Yu, Dunn, et al, 2008;Yu et al, 2012), can be administered to mice with established SAT, depleting B cells in the thyroid and greatly reducing SAT severity scores (Hong & Braley-Mullen, 2014).…”
Section: B Cells and Autoantibodies In Satmentioning
confidence: 99%
See 3 more Smart Citations